End of Life and People With Intellectual and Developmental Disability 2022
DOI: 10.1007/978-3-030-98697-1_3
|View full text |Cite|
|
Sign up to set email alerts
|

Suicide and Autism: A Lifespan Perspective

Abstract: People with Autism Spectrum Disorder (ASD) are at increased risk of suicidal behaviour compared to the general population; the largest population-based study to date demonstrates a sevenfold increased risk of premature death by suicide. This chapter provides an overview of: a) the current literature regarding risk and prevalence of suicide behaviour in autism; b) the role of intellectual disability/intellectual developmental disorder in suicide in autism; c) correlates, risk and protective factors; d) dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 130 publications
(139 reference statements)
0
2
0
Order By: Relevance
“…In autism, self-injurious behavior associated with the restricted and repetitive behavior domain (e.g., head-banging, biting, scratching) is relatively common, and may be considered part of, or a symptom of the autism diagnosis. Hence, clinicians may not consider it a 'red flag' for STB in the same way as they might in other (non-autistic) populations (Hedley et al, 2022). Other self-injurious behaviors related to co-occurring psychopathology, such as cutting, are also prevalent in the autistic population (Moseley et al, 2020) and may be associated with STB (Cassidy, Bradley, Shaw, et al, 2018).…”
Section: Validation Of a Modified Clinical Interview For The Assessme...mentioning
confidence: 99%
“…In autism, self-injurious behavior associated with the restricted and repetitive behavior domain (e.g., head-banging, biting, scratching) is relatively common, and may be considered part of, or a symptom of the autism diagnosis. Hence, clinicians may not consider it a 'red flag' for STB in the same way as they might in other (non-autistic) populations (Hedley et al, 2022). Other self-injurious behaviors related to co-occurring psychopathology, such as cutting, are also prevalent in the autistic population (Moseley et al, 2020) and may be associated with STB (Cassidy, Bradley, Shaw, et al, 2018).…”
Section: Validation Of a Modified Clinical Interview For The Assessme...mentioning
confidence: 99%
“…In addition, instruments not designed for use with autistic people can be problematic when used by this population due to use of different vocabulary, confusing terms, complex sentence structure or grammar, imprecise response options, and inclusion of ableist language or concepts (Nicolaidis et al, 2020). Indeed, recent research has identified a clear need for instruments that can be used to assess suicide behavior in autistic people, in both research and clinical settings (Cassidy et al, 2018b; Hedley et al, 2022).…”
mentioning
confidence: 99%